Cattaneo-Christov heat flux (CC model) in mixed convective stagnation point flow towards a Riga plate. (November 2020) - Shah, F.; Ijaz Khan, M.; Hayat, T.; Momani, Shaher; Imran Khan, M.
Highlights: Here Fourier law of heat conduction (CC) model is discussed subject to Riga plate. Stagnation point flow is considered. The flow is generated due to linear stretching. Series solutions are obtained through homotopy analysis method. Abstract: This research article proposes an improved Fourier law of heat conduction (Cattaneo-Christov) in presence of heat source/sink. The heat transport characteristics are modeled for mixed convective stagnation point flow by a Riga plate. Flow is generated due to linear stretching velocity. The partial differential system is changed to ordinary differential system through implementing appropriate transformations. Series solutions are developed through semi-analytical method called as homotopy analysis method. Present research article is related to the improved Fourier law of heat conduction (Cattaneo-Christov) over a linear stretchable surface of Riga plate when fluid saturates porous space. The main outcomes of present communication are summarized as: (i) velocity of material particles decreases subject to larger inverse Darcy-number while it enhances via velocity ratio and magnetic parameters (ii) temperature distribution as well as layer thickness enhance for higher estimations of Eckert number and heat source parameter while it decays against Prandtl number (iii) skin friction coefficient decreases through higher values of inverse Darcy number and mixed convection parameter.